Farms in transition: agroecological farming giving families an edge in the face of declining agricultural productivity and climate stress in Bikita, Zimbabwe. Issue 9 (21st October 2022) - Mapfumo, Paul; Mapangisana, Toga; Mtambanengwe, Florence; MacCan, Sarah; Siziba, Shephard; Muto, Yvonne; Makoni, Edward; Nezomba, Hatirarami; Hogan, Rose
ABSTRACT: Agroecology is an approach that seeks to improve the integration of food systems through environmentally sustainable production systems. This paper explores the key practices considered to define agroecological farming in Bikita District of Masvingo in Zimbabwe. It reviewed the literature on agroecology and presented a criterion that informed analysis to distinguish between agroecological and non-agroecological farmers. Agroecological farmers mainly comprised resource-constrained farmers who sought to tap on their natural environment, local knowledge, and social networks to move away from conventional agricultural practices to achieve similar food and nutrition security and livelihood objectives as their non-agroecological counterparts. They differed from their non-agroecological counterparts mainly with respect to the diversity of crops grown, agronomic techniques used, and primary sources of income. Major challenges for farming households practising agroecological approaches includes lack of capacity for sustained adherence to agroecological principles (e.g., in the context of otherwise conventional systems; for all intends and purposes, existing extension messages and support mechanisms do not favor agroecological farming). These farmers, therefore, practice agroecological farming against institutions and policies that do not recognize agroecological farming. There is therefore currently 'no level playing field' for farmers and promoters of agroecological practices in Bikita as in many areas in Zimbabwe.